Mutation induction by gamma rays in clonal plantlets of Eucalyptus saligna and Eucalyptus dunnii: dose adjustment and application of repeated pruning - Ziegler, Ana Cristina da Fonseca; Neto, Augusto Tulmann; dos Santos, Osmarino Pires; Pimentel, Nathalia; Peres, Fabiana Schmidt Bandeira; Tambarussi, Evandro Vagner [UNESP] (Springer Nature, 2025)
Applying genetic improvement methods is essential for the adaptation of various Eucalyptus species, including the selection of desirable genotypes. Among the tools used for improvement, mutagenesis aims to increase genetic variability through mutation, causing changes in qualitative and quantitative traits. The aims of this study were to evaluate and select methods to induce mutation using irradiation with gamma rays for two species of the Eucalyptus genus (E. saligna and E. dunnii), identify the optimal irradiation dose for plantlets, and determine the best position(s) for mutant selection in axillary buds of V1M1 branch segments originating from irradiated plantlets. The methodology involves two experiments. In the first experiment, E. saligna and E. dunnii plantlets were submitted to eight different doses of gamma ray irradiation. In the second experiment, the plantlets irradiated with the ideal dose were pruned to stimulate the growth of lateral branches (V1M1, V2M1, V3M1), using the repeated pruning method, and three pruning treatments. Both species respond similarly to irradiation. Specific optimal doses were identified as 22.56 Gy for E. saligna and 23.04 Gy for E. dunnii. For the repeated pruning method, the treatment that maintained the fifth and sixth buds showed superior results in both species.
Keywords: Forest species; Genetic variability; Irradiation; Ministumps; Mutagenesis; Repeated pruning